Timing restriction and information provision effects on birth type choice. - Melo, Lucas Braga de (2019)
Scheduled Cesarean Section before 39 weeks of gestation are common in Brazil, they are frequently associated with respiratory and other adverse neonatal outcomes [Tita et al., 2009]. In 2016, Brazil implemented a policy prohibiting Cesarean Section's (CS) before the 39th week of pregnancy by mothers' request, it also demanded physicians to inform mothers about Scheduled CS's risks. This research measures this Law's effects on the Scheduled CS's ratio and Natural Delivery (ND) ratio. The Differences-in-Differences method is applied using DiD and DiDiD Regressions in order to quantify the policy e ects. The policy decreased Scheduled CS's ratio up to 1.7 percentage point for births at the 37th week and 1.95 percentage point at the 38th week of gestation, equivalent to a 5% decrease in the number of Scheduled CS's. There are also evidence that the policy increased up to 1.1 percentage point the Scheduled CS ratio for births at the 39th week, equivalent to a 3.6% increase in the number of Scheduled CS. It is estimated an increase up to 3.3 percentage points in the ND ratio for births at the 37-38th weeks, equivalent to a 8.6% increase in the number of ND's.